المنطق المعكوس في الخطاب الحجاجي القرآني المغلوط (Journal of Imam Al-Kadhim College, 2023)
This research takes care of the inverted logic in argumentative practices of a fallacious nature, and the origins of its formation in communicative processes, which has become a branch of the science of pilgrims, well as the identification of areas of work, and the contexts required by this logic, especially that it is based on (results), and even that (results) are the pillar of the introductions that lead to it; on the basis of this logic that goes from the results to the introductions is called (inverted logic), and this is contrary to the formal mental logic. Hence the argumentative fallacies gained importance because they are based on the philosophy of difference based on objection and counter-objection, proof and counter-proof, and this logical pattern was common to the ancients, especially in the Greek philosophical heritage, and the emergence of Aristotelian logic was a reaction to the fallacious Sophist activity.
Keywords: الكلمات المفتاحية ( المنطق المعكوس ، الحجاج ، المغلوط )